1977
DOI: 10.1111/j.1432-1033.1977.tb11897.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cellular Binding of Exogenous Gangliosides

Abstract: Experiments were performed to characterize the accumulation of different exogenous sialoglycolipids by cells.A biphasic kinetics of accumulation appeared to be characteristic for intact primary and permanent monolayer cells and chicken erythrocytes whereas that of chicken erythrocyte ghosts was monophasic. Saturation levels could be reached with Galbl+3 GalNAcpl+4 Gal[3+2aNeuAc]-, !I1 +4 GlcPl -1'Cer and Galfil-+3 GalNAcfil -4 Ga1[3c2aNeuAc8+2aNeuAc]fil+4 Glc@ -1'Cer with concentrations of 100 and 200 nmol per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 25 publications
8
46
0
Order By: Relevance
“…However, to address concerns raised by reports that work-up conditions alter cellular and tissue distributions of gangliosides (51) and to ensure that the flow cytometry method provided biologically-relevant results in our hands, we tested the concentration and time dependence of the uptake of endogenous GM3 and GD3. In these tests, we observed ganglioside uptake and incorporation consistent with literature reports (52). Specifically, time-and dose-dependent increases in GM3 (Fig.…”
Section: Verification Of the Flow Cytometry Detection Methods By Analysupporting
confidence: 91%
“…However, to address concerns raised by reports that work-up conditions alter cellular and tissue distributions of gangliosides (51) and to ensure that the flow cytometry method provided biologically-relevant results in our hands, we tested the concentration and time dependence of the uptake of endogenous GM3 and GD3. In these tests, we observed ganglioside uptake and incorporation consistent with literature reports (52). Specifically, time-and dose-dependent increases in GM3 (Fig.…”
Section: Verification Of the Flow Cytometry Detection Methods By Analysupporting
confidence: 91%
“…Exogenous gangliosides can be incorporated into the plasma membrane in a manner analogous to endogenous gangliosides under appropriate conditions. Wiegandt and co-workers 29,30 have reported that exogenous gangliosides are taken up by cells, but are incorporated in the plasma membrane in a different way than endogenous gangliosides and are not degraded. They also observed that most of the gangliosides were removed by adding serum or serum albumin to the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…(i) as loosely associated micelles removable by serum proteins; (ii) as a protein-bound serumresistant, but protease-sensitive ganglioside fraction; and (iii) as gangliosides associated in a protease-resistant manner [75][76][77].…”
Section: Uptake Of Exogenous Gangliosides Into the Cell Membranementioning
confidence: 99%